Puzzling over spurdogs: molecular taxonomy assessment of the Squalus species in the Strait of Sicily. Issue 1 (1st January 2021) - Ferrari, A.; Di Crescenzo, S.; Cariani, A.; Crobe, V.; Benvenuto, A.; Piattoni, F.; Mancusi, C.; Bonnici, L.; Bonello, J. J.; Schembri, P. J.; Serena, F.; Massi, D.; et al.
Abstract: The actual occurrence of Squalus megalops in the Mediterranean Sea has recently been questioned. Several research works which sought to assess available morphological and meristic features that differentiate S. megalops from other Squalus species in the Mediterranean Sea, revealed poor discriminatory power and high variability of the assessed characters, especially when comparing S. megalops and S. blainville . The application of molecular tools does not support the presence of S. megalops . In the present study, we screened spurdog species from the Strait of Sicily using a molecular taxonomy approach based on two mitochondrial DNA markers and we report the occurrence of two Squalus lineages characterizing specimens collected from the stretch of sea between Tunisia, southern Sicily, Malta and Libya. The results support the hypothesis that a common species, S. blainville, currently inhabits the Mediterranean Sea, while a second and rare species is probably an occasional visitor with high morphological similarity to the S. megalops and S. blainville but is genetically distinct from both. Within this perspective, the occurrence of S. megalops in the Mediterranean Sea is not confirmed and our study highlights the taxonomic uncertainties in relation to the occurrence and distribution of Squalus species in this region. We encourage the establishment of a coordinated international effort to implement a comprehensive and integrated taxonomic assessment on this genus which represents an irreplaceable component of the biodiversity of the area.